Research and Development in Adult Education Fields and Trends - Oliver, Esther (Study guides in Adult Education, 2010)
The importance of adult education is growing steadily- be it in relation with migration, matters of inclus - ion, the work place etc. Thus, this international perspective on the most important research issues in adult education is a wealth of knowledge for anyone related to this field. The book is composed as a text book and thus, provides didactic material for discussion and further exploration of research in the field of AE from an international perspective. From the Contents: EU policy in Education and AE: links with Research opportunities on the field Support for Research in Adult Education in the European Union Main areas of Research in AE at the International level · Research on Migration. · Research on Inclusion, Access and Participation · Professionals, Assessment and Counselling · Learning in the Workplace International organisations and networks with influence to Adult Education